Persistent Herpesvirus Infections and Telomere Attrition Over 3 Years in the Whitehall II Cohort. (22nd July 2017) - Dowd, Jennifer B; Bosch, Jos A; Steptoe, Andrew; Jayabalasingham, Bamini; Lin, Jue; Yolken, Robert; Aiello, Allison E
Summary: Persistent herpesviruses, including cytomegalovirus, herpes simplex virus type 1, and human herpesvirus type 6 were associated with greater telomere attrition over time in a sample of healthy adults aged 53–76 years. Abstract: The determinants of telomere attrition, a potential marker of cellular aging, are not well understood. Persistent herpesvirus infections including cytomegalovirus (CMV) infection may be particularly important for telomere dynamics via mechanisms such as inflammation, oxidative stress, and their impact on peripheral blood lymphocyte composition. This study examined the association of 4 human herpesviruses (CMV, herpes simplex virus type 1, human herpesvirus type 6, and Epstein-Barr virus) with change in leukocyte telomere length (LTL) over 3 years in 400 healthy individuals (aged 53–76 years) from the Whitehall II cohort. CMV, herpes simplex virus type 1, and human herpesvirus 6 infection were independently associated with greater 3-year LTL attrition, with no association found for Epstein-Barr virus. The magnitudes of these associations were large, for example, the equivalent of almost 12 years of chronological age for those CMV seropositive. Seropositivity to more herpesviruses was additively associated with greater LTL attrition (3 herpesviruses vs none, β = −0.07 and P = .02; 4 infections vs none, β = −0.14 and P < .001). Higher immunoglobulin G antibody levels among those seropositive to CMV were also associated with shorter LTL at follow-up. These associations were robust to adjustment for age, sex, employment grade, body mass index, and smoking status. These results suggest that exposure to infectious agents should be an important consideration in future studies of telomere dynamics.